Effect of undernutrition on the cranial growth of the rat: An intergenerational study - Cesani Rossi, María Florencia (2003)
The cumulative effect of undernutrition on successive generations was tested. The cranial growth of three generations of undernourished rats (F1, F2, F3) was compared to that of the parental generation (P), in order to (1) measure the extent to which the growth of each facial and neurocranial functional component was retarded when animals were undernourished and (2) determine whether any cumulative effect between generations can be found. The P generation was fed ad libitum, and the undernourished generations were fed 50% (F1) and 75% (F2 and F3) of the parental diet. Nine radiographs were taken from the age of 20-100 days. The length, width and height of the neurocranial and facial components were measured on each radiograph. Neurocranial (VNI), facial (VFI), and neurofacial (NFI) indices were calculated. Data were processed by the Kruskal-Wallis and Kolmogorov-Smirnov tests. An impairment in neurocranial and facial growth was found, the latter being more affected than the former in F1. At variance, the neurocranium was more affected than the face in F2 and F3, resulting in variations of the shape of the skull. A cumulative effect of moderate transgenerational undernutrition was evident and points to the need for further analysis on this topic. Copyright © 2003 S. Karger AG, Basel.